Managing Da'wah Conflict to Strengthen Interreligious Harmony: A Case Study of Multicultural Da'wah Programs in Berastagi, Indonesia - Osama Al Azizi Tinodungan Siregar; Muaz Tanjung (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
Religious diversity can strengthen social cohesion, but differences in religious communication may also generate tension when they are not managed contextually. This study analyzes conflict-management practices in multicultural da'wah programs, identifies factors contributing to potential da'wah-related conflict, and explains the strategic roles of da'i and religious leaders in promoting interreligious harmony in Berastagi District, Karo Regency. A qualitative case-study design was employed. Informants were selected purposively from MUI, the Ministry of Religious Affairs, religious and community leaders, and multicultural program personnel. Data were collected through participant observation, semi-structured interviews, and document analysis and were analyzed through data condensation, data display, and conclusion drawing and verification. The findings show that conflict management operates through persuasive and moderate da'wah, interfaith dialogue, deliberation, institutional coordination, and early clarification of sensitive issues. Potential conflict is associated primarily with divergent interpretations of da'wah messages, religious symbols and activities in public spaces, communication barriers, and unverified religious information on social media. Da'i and religious leaders function as communicators, mediators, educators, and agents of religious moderation. The study concludes that effective preventive management integrates four mutually reinforcing elements: moderate da'wah, collaborative religious leadership, institutional coordination, and multicultural programs that strengthen social cohesion. This integrated model provides a context-sensitive framework for sustaining tolerance and peaceful coexistence in religiously diverse communities.